Optimalisasi Fungsi Pengawasan Komisi Yudisial terhadap Hakim - Kusuma, Brama Adi; Fajriah, Miftahur Rizqi Arrumi; Putri, Ristria Nimas Ayu Kartika (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
The purpose of this study was to analyze the optimization of the supervisory function carried out by the Judicial Commission for realizing a clear justice. This study used the legal research method, which means that research was conducted by examining existing library data and references, such as laws and regulations, books, magazines, and scientific journals. The optimization of the oversight function of the Constitutional Court was carried out by establishing a good relationship with the Supreme Court to identify the limits of their respective duties and authorities, forming the Liaison Judicial Commission, and the Network of the Judicial Commission. The role of Liaison Judicial Commission needed to be improved, not only receiving reports from the public but also actively finding violations of the code of ethics committed by judges. Socialization regarding the existence of the Judicial Commission should be carried out more through Network of the Judicial Commission to increase understanding of the community so that the community can play an active role in providing reports for the realization of a clear justice.